Risk factors associated with progression from pre‐eclampsia to eclampsia: A prospective cohort study and population‐wide data analysis - Annettee Nakimuli; Brittany A. Jasper; Sarah Nakubulwa; Moses Adroma; Jackline Akello; Imelda Namagembe; Musa Sekikubo; Eve Nakabembe; Ashley Moffett; Catherine E. Aiken (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Eclampsia is a life‐threatening complication of pre‐eclampsia. There are currently no means of reliably identifying women with pre‐eclampsia who are at the highest risk of progression to eclampsia and would thus benefit from prioritization for intensive monitoring and urgent delivery. This is particularly challenging in obstetric settings where resources are limited. We identify risk factors for the progression of pre‐eclampsia to eclampsia in low‐ and middle‐income settings. Material and methods Women diagnosed with pre‐eclampsia were prospectively recruited at a single tertiary referral centre in urban Uganda (2011–2016). Multivariable logistic regression models were used to identify risk factors that predicted the likelihood of progression to eclampsia. Key findings were validated in a geographically, socioeconomically, and ethnically distinct population using population‐wide hospital admission data from Ecuador (2021–2023). Results In urban Uganda, progression from pre‐eclampsia to eclampsia was associated with nulliparity (OR 2.4; 95% CI: 1.1–5.4, p = 0.03), Baganda ethnicity (OR 1.9; 95% CI: 1.1–3.9, p = 0.01), unskilled/unemployed paternal occupation (OR 2.8; 95% CI: 1.3–6.4, p = 0.03), and a trend toward younger maternal age (OR 0.9; 95% CI: 0.9–1.0 per year; p = 0.09). Risk of progression to eclampsia was not related to the severity of pre‐eclampsia or the number of antenatal clinic visits. In Ecuador, population‐wide analysis showed that progression to eclampsia was associated with younger maternal age (p < 0.001) and a trend toward public vs privately funded obstetric care (p = 0.09). Conclusions Eclampsia risk extends beyond clinical markers of pre‐eclampsia severity, with socioeconomic factors and maternal age playing crucial roles in disease progression. A targeted, context‐specific approach prioritizing high‐risk young women with socioeconomic vulnerabilities could optimize healthcare resources and mitigate severe hypertensive disorder risks.